Kelisa Cleaner Sdn. Bhd. / Mohd Redzuan Ishak…[et al.] - Ishak, Mohd Redzuan; Mat Ali, Muhamad Hafiz; Jani, Mohd Fitri; Md Aris, Mohd Nizam; Bahardin, Mohd Fadli; Mohd Yusob, Yusmafaizal (2020)
This company will be established as a partnership company that provide cleaning services in year 2004. Our company specialist in cleaning houses, factories and building. Type of cleaning we provide such as cleaning floor, glass, window, furniture, carpet and toilet. Taken from a kind of fish named Kelisa, this company established it name as Kelisa Cleaner Sdn. Bhd. and will be manage six shareholder which has a qualification in business and management under banking study. We will start our business with beginning capital RM70,000 that is from partnership contribution and long-term loan.